Improvement of the motor structure of the paddle technique of qualified female athletes in rowing - Gamali, V.; Potop, V.; Bondar, A.; Salnykova, S.; Shynkaruk, O.; Shevchuk, O.; Ulan, A. (Journal of Physical Education and Sport, 2020)
The article is devoted to solving the problems of improving the motor structure of the technique of rowing qualified female athletes in women's single skulls boats in the yearly circle at the stage of specialized basic training in rowing. In the study 36 female rowers (qualification - members of the national team of Ukraine) were investigated. Using high-quality SONY Didgital 8 cameras and Lumax software, quantitative and qualitative characteristics of the rowing technique for female athletes of different qualifications were determined. As a result of comparative analysis, significant differences in the biomechanical structure of the rowing locomotion technique of female rowers of different qualifications were established on the basis of which average group statistical models of technical preparedness were developed. In order to improve the technique of rowing of the athletes of the junior national team of Ukraine in single skulls boats we have justified and developed a training program. In order to approve it, a forming experiment was carried out, which involved 12 female rowers. Dividing of athletes on the control and the experimental group was carried out by random selection of six female athletes who at the beginning of the experiment had no statistically significant differences in technical parameters. The data obtained as a result of the pedagogical experiment confirmed the effectiveness of our proposed program to improve the kinematic structure of rowing technique in single boats in female athletes of the experimental group.